2022
DOI: 10.3389/fimmu.2022.869993
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of TACE Refractoriness-Related Diagnostic and Prognostic Scores and Characterization of Tumor Microenvironment Infiltration in Hepatocellular Carcinoma

Abstract: BackgroundTranscatheter arterial chemoembolization LIHC, Liver hepatocellular carcinoma; (TACE) is a valid therapeutic method for hepatocellular carcinoma (HCC). However, many patients respond poorly to TACE, thus leading to an adverse outcome. Therefore, finding new biomarkers for forecasting TACE refractoriness occurrence and prognosis becomes one of the current research priorities in the field of HCC treatment.Materials and MethodsBased on microarray datasets and a high-throughput sequencing dataset, the TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 66 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…VEGF was also reported to modulate the checkpoint expression of CD8+T cells in HCC ( 72 ). The expression of PD-1 increased in peripheral mononuclear cells ( 6 , 7 ). ICIs activate interferon-γ (IFN-γ)+ Type 1 T helper (Th1) cells to normalize the tumor vasculars and improve hypoxic environments ( 6 ).…”
Section: Why the Combination Therapy Of Lenvatinib Plus Tace With Pd-...mentioning
confidence: 99%
See 2 more Smart Citations
“…VEGF was also reported to modulate the checkpoint expression of CD8+T cells in HCC ( 72 ). The expression of PD-1 increased in peripheral mononuclear cells ( 6 , 7 ). ICIs activate interferon-γ (IFN-γ)+ Type 1 T helper (Th1) cells to normalize the tumor vasculars and improve hypoxic environments ( 6 ).…”
Section: Why the Combination Therapy Of Lenvatinib Plus Tace With Pd-...mentioning
confidence: 99%
“…However, repeated TACE treatment could decrease the liver function and cause failure to accept follow-up systematic treatment. The increased times of TACE treatment resulted in the decline in the response rate of tumor tissue to treatment (6)(7)(8)(9). The phenomenon was known as TACE refractoriness/TACE failure, which was defined by the Japan Society of Hepatology in 2010 (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the top 30 mutated genes in both risk groups. Furthermore, we determined several checkpoint genes (CD274, CTLA4, HAVCR2, LAG3, PDCD1, and TIGIT) and found that most checkpoint genes had higher expression in the high-risk group ( 31 ). The oncoplot of TMB and expression levels of checkpoint genes were shown in Figure 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 365 tumor samples from the TCGA-LIHC cohort and 221 tumor samples from the GSE14520 cohort were included. Moreover, to study TACE response, we obtained gene expression profile data from GSE104580, which included 100 TACE-responsive samples and 100 TACE-refractory samples ( He et al, 2022 ). Both somatic mutation data and CNV data were obtained from the TCGA-LIHC cohort, including 371 tumor samples.…”
Section: Methodsmentioning
confidence: 99%